Biochemical characterization of a novel l-asparaginase from Bacillus megaterium H-1 and its application in French fries. (November 2015) - Zhang, Sunyan; Xie, Yajuan; Zhang, Chong; Bie, Xiaomei; Zhao, Haizhen; Lu, Fengxia; Lu, Zhaoxin
ABSTRACT: A novel ans Z gene, encoding a putativel -asparaginase II from Bacillus megaterium H-1 (BmAase), was cloned and expressed in Escherichia coli . The recombinant enzyme showed high activity (44.7 IU/mg) with negligible glutaminase activity and was purified to homogeneity using one-step nickel-affinity chromatography. The molecular weight of BmAase was 39.63 kDa by MALDI-TOF MS. The optimum pH and temperature for BmAase activity were 7.0 and 40 °C, respectively. The enzyme was stable in the pH range of 5.0–8.0 and exhibited more than 70% and 55% retention of activity following 12 h of incubation at 60 and 70 °C, respectively. The melting temperature of the protein determined by DSC was 51.3 °C. The KM and Vmax values of BmAase were, respectively, 0.80 mM and 1.58 IU/μg for its natural substratel -asparagine. Acrylamide formation upon frying of potato strips treated with BmAase was about 92% lower than in untreated potato strips. These results reveal the potential of this enzyme for use in the food processing industry. Highlights: A novel ansZ gene encodingl -asparaginase from Bacillus megaterium H-1 (BmAase) was isolated and characterized. BmAase showed highly specific activity across a wide pH range and significant temperature stability. BmAase could reduce almost all amount of acrylamide formed during the frying process.